(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Reinforced concrete (RC) systems are vital to modern infrastructure, imparting power and sturdiness in typical situations. However, their overall performance can be significantly compromised when subjected to multi-hazard herbal disasters, which include earthquakes, floods, hurricanes, and tsunamis. This review examines the behavior and techniques performance of RC structures beneath such complex, multi-danger scenarios that specialize in harm mechanisms, structural vulnerabilities, and put-up-disaster residual capacities. The paper also evaluates modern layout considerations, highlighting the want to incorporate hazard mitigation strategies and advanced retrofitting techniques. Additionally, the evaluation discusses emerging materials and technologies, fiber-strengthened polymers, and self-restoration concrete, beautifying resilience towards future occasions. By synthesizing recent research and case research, this assessment emphasizes the importance of multi-chance resilience in structural layout and the crucial function of updated design codes in mitigating the consequences of increasingly more extreme natural disasters because of climate change. Furthermore, study has shown how to increase buildings’ seismic resilience and ensure occupant safety by examining architects’ fundamental conceptions and practices. To reduce earthquake hazards, it’s important to prioritize seismic hazard assessment, strict design requirements, structural solid systems, and innovative technologies.